Compact Flexible Wearable Loop Antenna for Enhanced WBAN Performance across Multiband Frequencies - V. Lokhande, Pradipkumar; K. Kanse, Yuvraj (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This paper demonstrates the compact flexible wearable loop antennas structures for Wireless Body Area Network (WBAN) applications for various frequency bands. Also, examining the performance of loop antenna, loop monopole antenna and loop monopole antenna with smaller ground structure. All these antennas are designed by FR4 epoxy material with 0.2 mm thin flexible substrate thickness and 0.035mm copper strip as radiating element using microstrip feed techniques. The deformed geometries are reanalyzed using High frequency structure simulator (HFSS v18) software. Initially, proposed two antennas design as per the dimensions as 60×20× 0.2 mm3. Proposed two antennas (loop and loop monopole) are operating from 2.1723 GHz to 3.6200 GHz without change in dimensions, which provides resultant bandwidths are 56.36 % and 59.30 % respectively. Finally, compact loop monopole antenna with smaller ground structure dimension reduced as 50.5 × 20 × 0.2 mm3which operating from 1.1135 GHz to 3.72 GHz, improves bandwidth as 106.38 % under the industrial, scientific and medical (ISM) band. Also facilitating multi-band functionally at 1.13, 2.45 and 3.53 GHz. Finally, comparison and improvement in various antenna performance parameters such as bandwidth, return loss, VSWR, gain and antenna efficiency under ISM band for various WBAN applications using paper based (thin substrate) flexible wearable antenna.